Public Investment in Russia: Peculiarities of Implementation and Ways to Improve Efficiency - KOSOV, Mikhail E.; SOLYANNIKOVA, Svetlana P.; SIGAREV, Aleksandr V.; KARPENKO, Victor P.; POPKOV, Sergey Y. (Journal of Advanced Research in Law and Economics, 2019)
The study of dynamics and peculiarities of the main forms of public investment in Russia in order to find mechanisms to improve the efficiency of public investment. The research offers options to solve the problem of improving the efficiency of public investment in Russia. Apart from the measures designed to improve the statutory legal framework for public investment, it is necessary to revise the approach to the management of all public finances.